Use of belleville springs in the vibration protective mechanism with a part of quasi-zero-stiffness - Korytov M.S.; Sherbakov V.S.; Pochekueva I.E. (Научно-технический вестник Брянского государственного университета)
Reducing vibrations transmitted to the operator of construction and road vehicles through his chair is an urgent task, since significant vibrations lead to human diseases, reduce productivity and accuracy of work performed by machines, etc. Advantages for use in vibration protection systems are mechanisms with quasi-zero stiffness, in which no hydraulic or electromagnetic elements are used. Among them, vibration protection systems based on a package of Belleville springs, having a relatively simple design, can be distinguished. In them, unlike other mechanisms with quasi-zero stiffness, the functions of creating positive and negative stiffness are combined in the same structural elements — Belleville springs. The static characteristic of a Belleville spring with certain ratios of its dimensions already contains a section of quasi-zero stiffness of small length. The cup spring package allows you to increase the size of the quasi-zero stiffness area of the vibration-protective system of the armchair of a human operator of a construction or road machine to the required values of the order of several tens of centimeters. Certain difficulties arise in connection with the location of the center of the quasi-zero stiffness section of an individual disk spring in the middle of its deformation range when the spring is flat. This leads to the necessity of either using custom-shaped springs with collars at the top and bottom, or, as suggested in this article, using intermediate ring washers between the springs. The article provides a methodology for determining the number and size of springs and washers that provide a certain size of the quasi-zero stiffness section of the entire vibration protection system. It also provides a methodology for determining the mass of the entire package of springs with washers. It has been established that reducing the diameter of the springs requires reducing the thickness of the metal to provide a section of quasi-zero stiffness. Because of this, when the diameter of the springs is reduced by a factor of five, the mass of the mechanism can be reduced by a factor of twenty-four.